Case report: HSV lymphadenitis in immunocompromised patient with CLL - Al-Assil, Talal; Handelsman, Shane; Ansari, Faisal; Flatley, Ellen; Stone, Steven; Omaira, Mohammad (Frontiers in Oncology, 2024)
BackgroundRichter’s transformation (RT) in chronic lymphocytic leukemia (CLL) is associated with poor prognosis and requires prompt modifications in patient care. CLL patients are susceptible to severe infections due to immune dysregulation induced by their malignancy and immunosuppressive therapies.Case presentationWe present a case of a 63-year-old man with CLL who previously achieved remission and presented with a right inguinal mass. He was diagnosed with Rai Stage I CLL with del6q, without TP53 mutation, and treated with 6 cycles of fludarabine, cyclophosphamide, and rituximab (FCR) 6 years prior. Transformed CLL was suspected based on his lymphadenopathy, elevated lactate dehydrogenase, and constitutional symptoms, but excisional biopsy unexpectedly revealed herpes simplex virus (HSV)-1 and HSV-2, indicating a diagnosis of HSV lymphadenitis concurrent with CLL relapse with no transformation but acquisition of 17p deletion consistent with clonal evolution. The patient received three courses of dexamethasone and acyclovir, leading to successful clearance of the infection, evidenced by the resolution of his B symptoms. Subsequently, he was treated for the CLL recurrence with rituximab and venetoclax, demonstrating a favorable response with significant improvement in adenopathy and resolution of lymphocytosis.DiscussionThis case highlights the possibility of reactivated dormant viral infections in the context of CLL relapse, underscoring the importance of comprehensive evaluation in CLL patients presenting with lymphadenopathy. Due to immunosuppressive defects and iatrogenic hypogammaglobulinemia, patients with CLL face an increased risk of viral infections, with HSV reactivation occurring more frequently and severely in the setting of hematologic malignancies and dysregulated T-cell immunity. Timely administration of antiviral therapy is crucial for HSV lymphadenitis to prevent rapid progression and debilitating symptoms. This case demonstrates the importance of considering atypical viral infection presentations in CLL patients and emphasizes the necessity of timely and adequate biopsies to differentiate between CLL transformation, HSV lymphadenopathy, and other causes of lymphadenopathy while avoiding unnecessarily aggressive lymphoma therapy.